Production Practice Effects on Cotton Growth and Development in Thermally Limited Kansas - Logan M. Simon; Jonathan Aguilar; Farzam Moghbel (Kansas Agricultural Experiment Station Research Reports, 2025)
Declining water well capacities across southwest Kansas and the High Plains have forced many producers to reassess crop selection for their irrigated acreage. One strategy that could stabilize irrigated acreage as well as on-farm economic returns and potentially reduce the rate of aquifer depletion is the incorporation of more drought-tolerant crops like cotton. However, in thermally-limited cottonproducing regions like southwest Kansas where the growing season is relatively short, regionally-focused management practices are essential to avoid yield and quality penalties due to the narrow production window between planting and physiological maturity. The objective of this study was to determine the impacts of planting date, seeding rate, variety, and irrigation level on cotton yield formation factors including square and boll initiation/position/retention as well as locks/boll, seeds/lock, and lint yield in the 2024 growing season at Garden City, KS. In this study, cotton yield components were most responsive to seeding rate followed by planting date and then variety maturity. Cotton yield components were least responsive to irrigation rate. Results showed stand density was slightly decreased under the high irrigation rate compared to the low irrigation rate and proportionally impacted by seeding rate in the order of 75,000 > 50,000 > 25,000 seeds/a. End of season bolls/plant were greater under the low seeding rate compared to the medium and high seeding rates. Locks/boll were unaffected by any treatments. Seeds/lock were greater with the early planting date than the late planting date. Cotton lint yield was greater with PHY 205 than PHY 332 and greater with the early planting date than with the late planting date. Lint yield was increased with increasing seeding rate in the order of 75,000 > 50,000 > 25,000 seeds/a. Plants/a was the only yield component significantly correlated with lint yield. Lint percent was greater with PHY 205 than PHY 332 and greater with the early planting date than the late planting date. Lint percent was greater with the highest seeding rate than the lowest seeding rate. These results underscore that successful stand establishment is essential to success with cotton in thermally-limited Kansas.
Keywords: cotton; crop growth; crop development; yield components